How does the museum post-pandemic recovery? Exhibition design of DPR RI Museum - Vicky Ferdian Saputra; M. Kholid Arif Rozaq; Rini Riris Setyowati (Pascasarjana Institut Seni Indonesia Surakarta, 2022)
Museums are essential for connecting with and educating the public about their collections. A schism has developed between the public and museum institutions due to the Covid-19 pandemic's limits on museums. The inaugural exhibition of the DPR RI Museum aims to answer the challenge of readiness to recover museums' post-pandemic situation and conditions by rebuilding public involvement and communication. This study uses a mixed method equipped with research and development (R&D) using the ADDIE model product development systematics. The steps taken in organizing the exhibition are; (1) analysis of the historical context of the DPR RI building; (2) exhibition design; (3) development of 3D exhibition layout design; (4) implementation (exhibition); and (5) evaluation. A series of conferences and workshops supported the exhibition to educate the general public about the DPR RI's role as a home for the people. The results of museum content research and the development of a 3D museum layout model for exhibitions based on the validation of museum exhibition layouts are feasible to implement as a museum exhibition. Organizing exhibition events is the bond between the museum and the public, as evidenced by visitors' enthusiasm and positive response. This exhibition provided an important contribution to the post-pandemic situation, specifically as an effective and informative mode of communication in presenting the history of the DPR RI buildings to the general population.